2014
DOI: 10.1016/j.intell.2014.04.006
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of low, average, and high IQ on economic growth and technological progress: Do all individuals contribute equally?

Abstract: Individuals that reside in the highest social stratum of intelligence (i.e., those that have a high IQ) have been shown to generate relatively more national income and are more innovative, with those that have the lowest levels of IQ being less influential on economic development. However, the degree to which all levels of IQ influence economic growth and technological innovation remains unclear. By assuming that the IQ of a population is modeled based on a bell curve, we arrange IQ into three strata, namely i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 33 publications
5
19
2
Order By: Relevance
“…We found that these ranges of standardized IQ betas were considerably smaller than the beta coefficients for the impact of IQ on technological progress (β = .036-.272) and economic growth (β = .649-.783) calculated by Burhan et al (2014b) in standard growth models, using the same IQ dataset.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…We found that these ranges of standardized IQ betas were considerably smaller than the beta coefficients for the impact of IQ on technological progress (β = .036-.272) and economic growth (β = .649-.783) calculated by Burhan et al (2014b) in standard growth models, using the same IQ dataset.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, the intellectual class has the greatest impact in reducing the level of crimes through the enhanced functionality and quality of these sociodevelopmental and legal institutions across countries. Given previous findings on the positive impact of increasing IQ of the intellectual class as opposed to other social classes, it seems desirable that the education system focuses on improving the IQ of the top percentile group (Burhan et al, 2014b;Pritchett & Viarengo, 2009) to improve the competence of future leaders and policymakers and thereby the quality and functionality of civic and economic institutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies have concluded that countries with higher IQs generate higher productivity than countries with lower IQs (e.g., Burhan, Mohamad, Kurniawan, & Sidek, 2014a;Jones & Schneider, 2006;Lynn & Vanhanen, 2002Meisenberg, 2012;Rindermann, 2012;Rindermann & Thompson, 2011;Weede & Kämpf, 2002). As the IQ-productivity relationship is robust, some other recent studies have established that it is possible to increase per capita national income by raising the impact of IQ on productivity through the O-ring effect of skill complementarities.…”
Section: Introductionmentioning
confidence: 99%
“…This is true not just across countries, but also among regions within a country (Dutton & Lynn, 2014;Kura, 2013;Lynn, 2010Lynn, , 2012aLynn & Cheng, 2013;Pesta, McDaniel, & Bertsch, 2010). Some have argued that intelligence stimulates development via mechanisms such as scientifictechnological accomplishment, and the adoption of capitalist institutions (Burhan, Mohamad, Kurniawan, & Sidek, 2014;Rindermann, 2012;Rindermann & Thompson, 2011). Others have asserted that, in fact, development enhances intelligence through pathways such as better nutrition and superior education (Daniele, 2013;Wicherts, Borsboom, & Dolan, 2010a.…”
Section: Introductionmentioning
confidence: 99%